Longer lives, sicker lives? Increased longevity and extended disability among Mexican-origin elders - Angel, Ronald J; Angel, Jacqueline L; Hill, Terrence D (The journals of gerontology. Series B, Psychological sciences and social sciences, 2015)
(a) To identify factors associated with different patterns of functional decline in a longitudinal sample of older Mexican-origin individuals, and (b) to determine the proportions of life after age 65 characterized by serious functional impairment. We use the Hispanic Established Populations for Epidemiologic Studies of the Elderly to examine changes in objective Performance Oriented Mobility Assessments in a cohort of 3,050 Mexican-origin elders initially interviewed in 1993/1994 and recontacted 6 times over 17 years. This sample combined with an additional cohort of 902 individuals 75 and older added at wave 4 in 2004/2005 (combined sample = 3,952) is used in life table analyses to estimate the number of years after 65 characterized by serious functional impairment. Three distinct patterns of functional decline emerge: (a) high initial functioning followed by decline, but not to the level of disability (48%); (b) moderate initial functioning followed by decline to the level of disability (37.5%); and (c) initial disability followed by continued poor functioning (14.5%). Life table analyses reveal that subjects spent over half of the period after 65 with serious functional limitations. Significant gender and nativity differentials emerge. Protracted morbidity that accompanies increases in life expectancy has serious implications for the physical, social, and economic well-being of older individuals and their families, as well as for health and long-term care policy.